Phylogenetic Relationships of Local Durian Species based on Morphological Characteristics and PCR-RFLP Analysis of the Ribosomal Internal Transcribed Spacer (ITS) DNA - Fidia Fibriana; Lutfia Nur Hadiyanti (Biosaintifika: Journal of Biology & Biology Education)
In this study, twenty local durian accessions obtained from Central Java in situ collection were characterized using the morphological characteristics and the restriction patterns which generated from the region spanning the internal transcribed spacers ITS LEU and ITS 4. Morphological characteristics of durian leaf, stem, tree, and fruit showed variations for the different accessions, whereas polymerase chain reaction (PCR) products of ribosomal DNA region showed a low length of variation. The size of the PCR products and the restriction analyses with the restriction endonucleases Bsp1431yielded a restriction pattern for each accessions. The results of this study can be utilized by local durian farmers as a preliminary reference for durian propagation. The data obtained need to be supported by further research using the other molecular markers to obtain more accurate data. The clear identity of durian species can help the management of propagation systems by farmers to get superior local durian. How to Cite Fibriana, F., & Hadiyanti, L. N. (2016). Phylogenetic Relationships of Local Durian Species based on Morphological Characteristics and PCR-RFLP Analysis of the Ribosomal Internal Transcribed Spacer (ITS) DNA. Biosaintifika: Journal of Biology & Biology Education, 8(3), 362-370.